Agriculture and household nutrition security: Development practice and research needs - McDermott, John; Aït-Aïssa, Myriam; Morel, Julien; Rapando, Nancy (Springer, 2013)
Aligning agriculture to improve household nutrition security requires agricultural research and development specialists to understand nutrition objectives and be able to contribute to integrated agriculture-health programs. This paper builds on discussions during the household nutrition security session at the second Global Conference on Agriculture Research for Development (GCARD2). To begin, there is a summary of the variety of ways essential nutrition knowledge can underpin nutrition-sensitive agriculture. Lessons for improving nutrition through agriculture, including: efficient and effective production of diversified, highly nutritious and biofortified foods, enhancing value chains to improve nutritional quality and food safety, and better policies and investments, are highlighted. Frequently missing in discussions on nutrition-sensitive agriculture are the requirements for capacity development and extension—critical requirements to scaling-out and sustaining improved nutrition outcomes through agriculture. Gender, local empowerment and other key issues are discussed, as are the opportunities for cost-effective approaches to be implemented and expanded. Finally, research gaps, approaches and priorities to improve practice and anticipate and respond to dynamic changes in biological and social systems are discussed. Four next steps are summarized: (1) align agricultural interventions with those in health services, water and sanitation and social protection; (2) implement approaches to accelerate learning for development implementation and policy and investment enabling; (3) build local and national capacity to adapt and innovate; and (4) empower women and disadvantaged communities, in which the burden and solutions to nutrition security are found.